2011
DOI: 10.3174/ajnr.a2612
|View full text |Cite
|
Sign up to set email alerts
|

Spinal Arteriovenous Fistulas of the Filum Terminale

Abstract: SUMMARY:The filum terminale is an anatomic structure at the end of the spinal cord. Only a few cases of AVFs of the filum terminale have been reported. These AVFs usually consist of a single communication between the anterior spinal artery and a single draining vein. We retrospectively analyzed the clinical and radiologic features and treatment of 4 patients with spinal AVFs of the filum terminale. Clinical manifestations and MR images are similar to those of spinal dural AVFs. All patients underwent surgical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 9 publications
2
36
0
Order By: Relevance
“…The filum terminale extends downward from the apex of the conus medullaris to the cul de sac of the dura at S2, so the FTAVF should be fed mainly by the filum terminale artery as the caudal continuation of the anterior spinal artery below the arcade of the cone. Whether the filum can have other blood supplies besides the filum terminale artery is still debatable 13,14 ; as Djindjian et al 5 reported, the coccygeal nerve with a radicular artery supply was adherent to the filum in its proximal portion. Thus, an explanation for FTAVFs localizing in the distal portion of the filum having an additional blood supply could be a radicular artery or dural artery, as shown in our series and in 1 previous case report.…”
Section: Comparison Of Angioarchitecturementioning
confidence: 99%
See 1 more Smart Citation
“…The filum terminale extends downward from the apex of the conus medullaris to the cul de sac of the dura at S2, so the FTAVF should be fed mainly by the filum terminale artery as the caudal continuation of the anterior spinal artery below the arcade of the cone. Whether the filum can have other blood supplies besides the filum terminale artery is still debatable 13,14 ; as Djindjian et al 5 reported, the coccygeal nerve with a radicular artery supply was adherent to the filum in its proximal portion. Thus, an explanation for FTAVFs localizing in the distal portion of the filum having an additional blood supply could be a radicular artery or dural artery, as shown in our series and in 1 previous case report.…”
Section: Comparison Of Angioarchitecturementioning
confidence: 99%
“…Previously, these types of vascular malformations have been described mainly in smaller case series or case reports. Since Djindjian et al 9 reported the first case of FTAVF, several case reports [10][11][12][13] and 2 patient series studies 14,15 have been published. rAVSs that are located on a nerve root of the cauda equina have been reported in 2 cases to date.…”
mentioning
confidence: 99%
“…1,17 Our patients had symptoms similar to those reported in previous studies. 1,12,26 Interestingly, one patient (Case 2) had no neurological deficit despite obvious increased T2 signal within the lower thoracic cord on MRI. His symptoms (back and radicular pain) and abnormal MRI findings resolved after complete closure of the fistula.…”
Section: 19mentioning
confidence: 99%
“…3 This direct communication leads to an increase in venous pressure in the perimedullary veins that may result in spinal cord congestion and edema. 11,12 Clinical presentation is usually the result of progressive myelopathy or conus medullaris syndrome. 11,12,14 Magnetic resonance imaging is the best modality by which to diagnose the radiological sequelae of the disease.…”
mentioning
confidence: 99%
See 1 more Smart Citation